The course of recovery of locomotor function over a 10‐week observation period in a rat model of femoral nerve resection and autograft repair - Johannes Christoph Heinzel; David Hercher; Heinz Redl (Brain and Behavior, 2020)
Abstract Background A great extent of knowledge on peripheral nerve regeneration has been gathered using the rat sciatic nerve model. The femoral nerve model of the rat offers an interesting alternative, as it lacks disadvantageous features such as automutilation. For the analysis of locomotor behavior in rats after sciatic nerve injury, the CatWalk™ XT Gait Analysis System is often used. However, lesions of the femoral nerve in the rat have yet remained unstudied with this method. Material and Methods Ten male Sprague Dawley rats were evaluated with the CatWalk XT to study their gait after a 6‐mm resection of the right femoral nerve and reconstruction with an autologous nerve graft. Animals were observed for 10 weeks after surgery. Results Print Area, Print Length, Swing Speed, and Duty Cycle decreased to a minimum of 40% of baseline 2 weeks after surgery. Swing Time was elevated more than twofold at this time point. However, all these parameters recovered back to >90% of baseline values at 10 weeks after surgery. This degree of functional recovery has not been reported after sciatic nerve resection and autograft repair. Base of support varied minimally postoperatively in contrast to a strong decrement after sciatic nerve resection and repair. Conclusion We hereby provide a comprehensive in‐depth analysis of how to study functional recovery after injury of the femoral nerve in the rat via the CatWalk XT. We place special emphasis on highlighting the differences between the femoral nerve and sciatic nerve injury model in this context.